Case Report: Giant Paraganglioma of the Skull Base With Two Somatic Mutations in SDHB and PTEN Genes - Main, Ailsa Maria; Benndorf, Götz; Feldt-Rasmussen, Ulla; Fugleholm, Kåre; Kistorp, Thomas; Loya, Anand C.; Poulsgaard, Lars; Rasmussen, Åse Krogh; Rossing, Maria; Sølling, Christine; Klose, Marianne Christina (Frontiers in Endocrinology, 2022)
Head and neck paragangliomas (HNPGLs) are neuroendocrine tumors. They arise from the parasympathetic ganglia and can be either sporadic or due to hereditary syndromes (up to 40%). Most HNPGLs do not produce significant amounts of catecholamines. We report a case of a giant paraganglioma of the skull base with an unusually severe presentation secondary to excessive release of norepinephrine, with a good outcome considering the severity of disease. A 39-year-old Caucasian woman with no prior medical history was found unconscious and emaciated in her home. In the intensive care unit (ICU) the patient was treated for multi-organ failure with multiple complications and difficulties in stabilizing her blood pressure with values up to 246/146 mmHg. She was hospitalized in the ICU for 72 days and on the 31st day clinical assessment revealed jugular foramen syndrome and paralysis of the right n. facialis. A brain MRI confirmed a right-sided tumor of the skull base of 93.553 cm3. Blood tests showed high amounts of normetanephrine (35.1-45.4 nmol/L, ref <1.09 nmol/L) and a tumor biopsy confirmed the diagnosis of a paraganglioma. Phenoxybenzamine and Labetalol were used in high doses ((Dibenyline®, 90 mg x 3 daily) and labetalol (Trandate®, 200 + 300 + 300 mg daily) to stabilize blood pressure. The patient underwent two tumor embolization procedures before total tumor resection on day 243. Normetanephrine and blood pressure normalized after surgery (0.77 nmol/L, ref: < 1.09 nmol/L). The damage to the cranial nerve was permanent. Our patient was comprehensively examined for germline predisposition to PPGLs, however we did not identify any causal aberrations. A somatic deletion and loss of heterozygosity (LOH) of the short arm (p) of chromosome 1 (including SDHB) and p of chromosome 11 was found. Analysis showed an SDHB (c.565T>G, p.C189G) and PTEN (c.834C>G, p.F278L) missense mutation in tumor DNA. The patient made a remarkable recovery except for neurological deficits after intensive multidisciplinary treatment and rehabilitation. This case demonstrates the necessity for an early tertiary center approach with a multidisciplinary expert team and highlights the efficacy of the correct treatment with alpha-blockade.